Cultural Globalization Between Vision and Objectives - CHFIRA , Bahija (Revue Internationale du Chercheur, 2024)
Culture is the heritage memory based on the interaction of ideas, beliefs, knowledge and arts on which human values and sciences are based. However, the globalised system imbued with technology and electronics has trivialised this heritage memory, calling for the introduction of cultural globalisation, which some critical perspectives see as a currency, if not a factor of cultural alienation and alienation : One supports globalisation as a civilisational tradition, and the other opposes it because of the civilisational trap embedded in globalisation. This study sought to monitor the perception of cultural globalisation and its objectives in the international environment in general and the Arab world in particular. I explained the principles of each position separately, highlighting that for intellectuals, cultural globalisation is a violation of values, an invasion of cultures, the appropriation of identities, and the domination of peoples and societies through cultural hegemony, the commodification of culture, and the cultural penetration of cognitive memory despite its intellectual richness, and this identity cultural richness may result from socio-cultural realities and the collective cultural commonality. This cultural richness results from socio-cultural realities and the collective cultural commonality that bets on the formation of a cultural identity through cultural debate between civilisations and cultural interaction that aims to establish a common civilisational act while respecting the specificity of each cultural identity to avoid its obliteration or bullying. This study sought to monitor the perception of cultural globalisation and its objectives in the international environment in general and the Arab world in particular.